2010
DOI: 10.2478/v10089-010-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Consequences of Suburbanization in Selected Towns in the Eastern Borderlands of Poland

Abstract: The aim of the article is to present some of the consequences of the suburbanization process in Poland, where said the process became relevant in the 1990s and continues to this day. The author focuses specifically on the demographic aspects of this phenomenon, i.e., the changes in population it has implied in urban and suburban areas, as well as the characteristics of the relevant demographic structures and natural increase that affect the territories in question. The results of the research pertain to three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Numerous researchers (e.g. Sobala-Gwosdz, 2005;Czapiewski, 2010;Flaga, 2010;Brodziński, 2011;Mohiuddin, Hashia, 2012;Pomianek, 2012;Biegańska, 2013) have shown that local development is determined (or affected) by various exogenous factors, including: (a) geographical (e.g. peripheries or suburbs, distance to main transport routes); (b) natural environment (its values as well as legal status); (c) historical conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers (e.g. Sobala-Gwosdz, 2005;Czapiewski, 2010;Flaga, 2010;Brodziński, 2011;Mohiuddin, Hashia, 2012;Pomianek, 2012;Biegańska, 2013) have shown that local development is determined (or affected) by various exogenous factors, including: (a) geographical (e.g. peripheries or suburbs, distance to main transport routes); (b) natural environment (its values as well as legal status); (c) historical conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Related research has mainly focused on the following: (1) the characteristics and patterns of population migration and agglomeration [1][2][3][4][5], (2) the employment of the population and interactive development of industries and cities [6,7], (3) new town planning and construction [8][9][10][11][12], (4) changes in the values and lifestyles of the migrant population [13][14][15][16] and (5) urbanization and its impacts [17][18][19][20][21][22][23][24]. However, relatively little research has specifically focused on the residence of farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Important research on cities, the management of urbanization, the development problems in the transition period etc. were conducted in Russia (Khorev 1975, Maergoyz 1987, Pivovarov 1994, Lappo 1997, Pertsik 2009 and Poland (Flaga 2010, Grabkowska 2011).…”
Section: Introductionmentioning
confidence: 99%